Wireless Communication Using WiMAX Technology - Tarish Haider, Haider (Journal of Engineering and Sustainable Development, 2010)
WiMAX is a wireless digital communications system, also known as IEEE802.16 that is intended for wireless (Metropolitan area networks). WiMAX can provide Broadband Wireless Access (BWA) up to 50km for fixed stations and (5-15km) for mobile stations. In contrast, the Wi-Fi /802.11 wireless local area network standard is limited in most cases to only 100-300 feet (30-100m). With WiMAX, Wi-Fi like data rates are easily supported, but the issue of interference is lessened The ability to provide these broadband connections wirelessly, without laying wire or cable in the ground, greatly lowers the cost to provide these services. WiMAX may change the economics for any place where the cost of laying or upgrading landlines to broadband capacity is prohibitively expensive, as in emerging countries. WiMAX is a second-generation protocol that allows for more efficient bandwidth use. Interference avoidance, and is intended to allow higher data rates over longer distances. The IEEE 802.16 standard defines the technical features of the communications protocol. The WiMAX forum offers a means of testing manufacturer’s equipment for compatibility.